Analisis Gatekeeper Dalam Pemilihan Informasi Viral Media Sosial Di Tribun Sumsel - M. Marcelino Pahlevi; Aliasan; Jawasi (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
This study aims to analyze the role of gatekeepers in the selection of viral social media information published by Tribun Sumsel. In the context of journalism, gatekeepers function as parties who filter, select and assess the feasibility of information before being distributed to the public. The viral phenomenon on social media has provided wider access for users to share information quickly, thus increasing the challenge for the mass media in maintaining the quality and accuracy of news. This study uses a qualitative descriptive approach with observation, interview and documentation methods to understand how Tribun Sumsel selects and verifies viral information on social media. Then the data is analyzed using Julian Wallace's Contemporary Gatekeeping Theory which is divided into three stages, namely access to information, the selection process, and the publication process. The results of this study Tribun Sumsel has gone through various stages that show the gatekeeping process involves tiered verification and in-depth content analysis to avoid the spread of hoax information. This is done to ensure that the news published has gone through applicable procedures and follows journalistic guidelines, even under the pressure of dynamic media competition.